Thermal field over Tibetan Plateau and Indian summer monsoon rainfall - Sanjay D. Bansod; Zhi‐Yong Yin; Zhenyao Lin; Xueqin Zhang (International Journal of Climatology, 2003)
The interannual variability of the temperature anomalies over the Tibetan Plateau (25–45 °N, 75–105 °E) is examined in relation to the Indian summer monsoon rainfall (ISMR: June to September total rainfall). For this purpose, the temperature anomaly data of the central‐eastern Tibetan Plateau is divided into three regions using principal component analysis and the ISMR data for the period 1957–89 have been used. It is found that the January temperature anomaly of Region 2 has a significant negative relationship ( r = −0.67) with the ISMR of the subsequent season. This region is located over the northeastern part of the Tibetan Plateau, mostly in Qinghai province, including the Bayan Harr Mountain range and the Qaidam Basin. This relationship is consistent and robust during the period of analysis and can be used to predict the strength of the Indian summer monsoon in the subsequent season. It was found that the January temperature anomaly in this region was associated with a persistent winter circulation pattern over the Eurasian continent during January through to March. Finally, the variation patterns of the temperature anomalies in all three regions over the central‐eastern Tibetan Plateau during extreme years of the ISMR are examined. It is concluded that the January temperature anomaly over the northeastern Tibetan Plateau can be useful in forecasting the drought and flood conditions over India, especially in predicting the monsoon rainfall over the areas lying along the monsoon trough. Copyright © 2003 Royal Meteorological Society